ANALISIS BERPIKIR KRITIS PADA PERTANYAAN DISKUSI MAHASISWA PBSI FKIP UNIVERSITAS JAMBI - Deri Efri Yogi; Imam Suwardi Wibowo; Priyanto Priyanto (Universitas Negeri Makassar, 2024)
This study aims to determine the ability of critical thinking in student discussion questions in the language error analysis course of PBSI FKIP Jambi University. The research method used in this study is a qualitative approach that is content analysis. Research data in the form of writings of questions and answers to student discussions in the course of language error analysis PBSI FKIP Jambi University. The data collection methods used in this study include observation and documentation. In the process, the researcher will record the questions and answers of students in the course of language error analysis of PBSI FKIP Jambi University. Researchers also collected documentation data in the form of records of student discussion questions in the course of language error analysis PBSI FKIP Jambi University. The data analysis technique used is the data analysis technique according to Miles & Huberman. In the process the data obtained will be reduced presented and conclusions drawn. The data validity test used in this research is triangulation between researchers. The results of this study are that students are able to think critically on student discussion questions in the language error analysis course of PBSI FKIP Jambi University. Critical thinking that occurs includes several categories, namely, perspective clarification, consequences and alternatives, reasons and evidence, and agreement and disagreement.